RESEARCH OF DIGITAL CAMERA DYNAMIC RANGE ON THE IMAGING PROCESSING BASIS - M Sutkowski; Ya. N. Saukova (Приборы и методы измерений, 2017)
Digital images provide to determine photometric and colorimetric properties of objects subject to validation all elements of a measuring channel (digital camera, software, display) and solve the problem of their limited dynamic ranges. The aim of the study was to explore the dynamic range of a digital camera for use in photometric and colorimetric measurements.The Laboratory of Photonics at the Institute of Microelectronics and Optoelectronics (Warsaw Technical University, Poland) conducted a comparative experiment to determine the threshold of sensitivity, linearity and range of application the digital camera. Color target sets with certified brightness and chromaticity were created at the terminals and recorded with a digital camera with different exposure times. The authors propose a method to extend the dynamic range of a digital camera for red, green and blue color channel of intensities by pairing the calibration dependencies, and determine the true brightness and color of a point on the object by calculation.Calibration dependencies (triads) of digital camera for red, green and blue color channels intensities were constructed. These dependences allow determining lower and upper bounds of the dynamic range. Each triad has a form of the hysteresis loop. The experiment showed that the accuracy of this method is ± 3–5 %.